PERGESERAN FALSAFAH PERENCANAAN - Mulyadi, Mulyadi (Journal of Indonesian Economy and Business, 2002)
Old ways die hard. Why? Old ways which we use to build the future of organization die hard because we are not bold enough to question the fitness of our philosophies underlying them. Planning used in the traditional management is based on the following philosophies: (1) creating the future from the past, (2) leverage is placed on tangible assets, (3) planning is rule keeping efforts, (4) planning is a single-scenario planning, (5) planning is executed ad hoc, especially at strategic level. In this article, I discussed the shift of philosophies underlying the ways management used to plan the future in order for their organization to survive and prosper in facing a competitive and turbulent environment. The new environment demands a radical change of the ways they use to plan the future of their organization.Key words: planning; strategic planning